Simulation Tools Used at the Injection Mould Design - Monka, Peter; Hloch, Sergej; Andrej, Andrej; Somsak, Matej; Murgas, Filip (Manufacturing Technology Journal, 2016)
The article deals with the basic steps of injection mould design. The goal of the research was the proposition of the mould form so to be achieved the minimum waste and the shortest time of both mould filling and product cooling. Studied mould component is intended to serve as a stopper in the automotive spotlight. The simulations were realized for three designed types of running system and for four versions of cooling system. Due to the design optimization, the pressures, originated inside the cooling system and inside the mould cavity during the injection moulding process, were also investigated. 3D model of the mould was created in Autodesk Inventor Professional software and then solidification of material was simulated in Autodesk Moldflow. On the basis of the best solution, real form was manufactured and placed into injection moulding machine Arburg Allrounder 320 C.
Keywords: design; simulation; injection moulding; running and cooling system; pressure; waste